The Impelementation Of Podcasts To Enhance Students’ Speaking Skill At Sman 2 Binjai - Nurbaiti Ali; Rizky Vita Losi (COMPASS: Journal of Education and Counselling, 2024)
One issue that high school students frequently encountered was their inability to speak English word for word. They appeared extremely perplexed when trying to articulate their thoughts. Many students, particularly in speaking classes, lacked the enthusiasm or confidence to perform in English. That issue was also experienced by students at SMAN 2 Binjai whereas there are several ways to help students learn English, especially when it comes to speaking. Research has shown that podcasts are a useful tool for learning second languages. For instance, research indicates that podcasts might enhance students' vocabulary, linguistic proficiency, and learning activities. Additional researchers discovered that podcasts help pupils improve their speaking abilities. The research conducted was a Classroom Action Research (CAR). The research was done in SMAN 2 Binjai. The subject of the research were thirty students of social major students. The research was done in 2 cycles. From the results of the average score, it showed that there was a significant increase which was a good achievement to improve the students' speaking skills score. From the interview results, the students found it was fun to use podcasts. They began to be more confident to speak English and were motivated to learn more by using podcasts. Podcasts help students become more proficient speakers.